Pharmacogenetics in Psychiatry - Müller, Daniel J. (Pharmacopsychiatry, 2020)
This Special Issue on Pharmacogenetics in Psychiatry consists of five selected articles which encompass the first concepts of pharmacogenetics, to implementation strategies applyng pharmacogenetic testing into psychiatric clinical practice.